Factors that affect the behavior of adolescents in Thailand due to the use of mobile phones in their daily life - METTATHAMRONG, J. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT This study aims to examine the structural validity of the mobile phone usage behaviors of the daily life of an adolescent in Thailand. The participants in this study were 400 adolescents. The data analysis techniques used exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The results of exploratory factor analysis were classified into seven groups of parameters: capacity, communication, social, education, commercial, aesthetic, and entertainment factors with mobile phone usage behaviors. RESUMEN Este estudio tiene como objetivo examinar la validez estructural de los comportamientos de uso de teléfonos móviles en la vida diaria de un adolescente en Tailandia. Los participantes de este estudio fueron 400 adolescentes. Las técnicas de análisis de datos utilizaron análisis factorial exploratorio (EFA) y análisis factorial confirmatorio (CFA). Los resultados del análisis factorial exploratorio se clasificaron en siete grupos de parámetros: capacidad, comunicación, factores sociales, educativos, comerciales, estéticos y de entretenimiento con comportamientos de uso de teléfonos móviles.